240 A PEDIATRIC CASE OF BIVENTRICULAR END-STAGE ARRHYTHMOGENIC CARDIOMYOPATHY. (15th December 2022) - Agbariah, Andrea; Ermacora, Davide; Ruzzarin, Alessandro; Milewski, Priscilla; Nannelli, Chiara; Comunello, Andrea; Cemin, Roberto
Abstract: Background: Arrhythmogenic cardiomyopathy (ACM) is a rare heart muscle disease characterized by cardiomyocyte necrosis and fibro-adipose substitution which contribute both to the genesis of malignant ventricular arrhythmias and the morpho-functional alterations of the ventricles. ACM has always been considered a right ventricular disease with secondary involvement of the left ventricle, but recently a left dominant phenotype has been also described. Case report: A 14-year-old patient was admitted to our hospital after out-of-hospital cardiac arrest due to ventricular fibrillation, which occurred when she was at rest. A family history of sudden death and dilated cardiomyopathy was retrieved (her brother died at the age of 18 with a dilated heart), but other family members had never been screened to date. Cardiac magnetic resonance imaging (cMRI) appearance was consistent with biventricular dilatation along with severe systolic dysfunction (left ventricular ejection fraction 20%; right ventricular ejection fraction 25%). It showed also thinning and bulging of the basal free wall of the right ventricle proximal to the outflow tract (up to 4 mm) and multiple foci of subepicardial, mid-wall and transmural late gadolinium enhancement (LGE) in both ventricles. Signs of acute decompensated heart failure and a high arrhythmic burden were present. After cardiopulmonary stabilization, she underwent the implantation of a cardioverter-defibrillator (ICD). Conclusion: We herein report an uncommon case of biventricular AC ('definite diagnosis' according to both Task force criteria 2010 and Padua criteria) with advanced morpho-functional dysfunction occurring already in pediatric age, without any alerting symptom until the cardiac arrest (the typical onset of the ACM in children). It shows how severe biventricular involvement may affect young patients with a rapid progression of the disease. It also stresses the need for a strict follow-up of the family members of a proband since his first diagnosis, highlighting the pivotal role of cMRI in the diagnosis of pediatric disease. This has not been thoroughly studied and lacks sensitive and specific diagnostic criteria.